Development Of Effective Compositions Based on Local and Secondary Raw Materials For (Texas Journal of Engineering and Technology, 2022)
This article provides the development of effective compositions based on local and secondary raw materials for tanning and leather finishing. The use of reactive water-soluble polymers of local importance for the processes of tanning and finishing the leathers of the upper and lower parts of footwear is shown. The optimal options for the composition of the composition for the process of applying pigmented soil, containing hydrolyzed reactive water-soluble preparations K-4 under various conditions, and their distribution in the skin layers were determined.